Half of a yellow sun - Adichie, Chimamanda Ngozi, 1977- (Harper Perennial, 2007)
Set in Nigeria during the 1960s, at the time of a vicious civil war in which a million people died and thousands were massacred in cold blood, the three main characters are swept up in the violence during these turbulent years. One is a young boy from a poor village who is employed at a university lecturer's house. The other is a young middle-class woman, Olanna, who has to confront the reality of the massacre of her relatives. And the third is a white man, a writer who lives in Nigeria for no clear reason, and who falls in love with Olanna's twin sister, a remote and enigmatic character. As these people's lives intersect, they have to question their own responses to the unfolding political events. This extraordinary novel is about Africa in a wider sense: about moral responsibility, about the end of colonialism, about ethnic allegiances, about class and race; and about the ways in which love can complicate all of these things.